The efficiency of Islamic banks in Indonesia since 2012 to 2016 and influence to its marketing share using price and promotion as moderating variables - Farah Saufika Pramudita (Fak. Ekonomi dan Bisnis Islam UIN Sunan Kalijaga, 2018)
yt 1./ws.c.1